Evaluation of the functional properties of squash flour (Cucurbita maxima Duchesne) - Vergara, Vincent Austria; Francisco, Ma. Leonora dL. (1996.)
Squash flour was produced from Cucurbita maxima Duchesne using the dry-blanch-dry method standardized by Molano, Garcia and Cilindro (1989). The preparation of the squash flour was done in three batches to establish the reproducibility of the procedure. However, a lower flour recovery level was obtained, ranging from 5.6% to 6.6% compared to the standard 7%. The squash flours from the three batches were then subjected to functional property tests standardized by Malubay (1993) and Bengo (1994) using all-purpose flour as the standard. The success of incorporating squash flour into processed food lies not only on its nutritional component, but to a larger extent, on its functionl properties which determine its behavior in different formulation, processing and storage conditions. Thus, functional properties serve as a framework that will determine its application in foods. Of the four flour samples tested, all-purpose flour ranked first in viscosity, emulsifying capacity, fat absorption and dough formation. Batches 1 and 2 of squash flour ranked first in the tests for solubility, water absorption, gelation, emulsion stability and bulk density. Batch 3 exhibited marked difference from Batches 1 and 2 and in most cases, it was significantly different from the rest of the flour samples as shown in the results of Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Squashes; Flour